2014
DOI: 10.3325/cmj.2014.55.128
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced activation of matrix metalloproteinase-9 correlates with the degree of papillary thyroid carcinoma infiltration

Abstract: AimTo determine whether matrix metalloproteinase-9 (MMP-9) may be a useful adjunctive tool for predicting unfavorable biological behavior of papillary thyroid carcinoma (PTC) by evaluating the expression profile and proteolytic activity of MMP-9 in PTC by different techniques and correlating the findings with clinicopathological prognostic factors.MethodsImmunohistochemical localization of MMP-9 was analyzed with antibodies specific for either total or active MMP-9. Activation ratios of MMP-9 were calculated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 27 publications
0
28
0
1
Order By: Relevance
“…All these three types of peripheral rings could be found in the PTCs without cervical LNM ( P > 0.05), whereas irregular no-enhancement ring was the most common type in the PTC with cervical LNM ( P < 0.05). The adjacent thyroid tissue could be invaded by cancer, which might cause the appearance of the peripheral irregular no-enhancement ring as a result of the interstitial edema and fibrosis, hyaline degeneration or necrosis 24 , 25 . Peripheral ring was not a common feature of PTC, but the irregular no-enhancement ring may predict the risk of cervical LNM comparing with other three types of peripheral rings ( P = 0.04).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these three types of peripheral rings could be found in the PTCs without cervical LNM ( P > 0.05), whereas irregular no-enhancement ring was the most common type in the PTC with cervical LNM ( P < 0.05). The adjacent thyroid tissue could be invaded by cancer, which might cause the appearance of the peripheral irregular no-enhancement ring as a result of the interstitial edema and fibrosis, hyaline degeneration or necrosis 24 , 25 . Peripheral ring was not a common feature of PTC, but the irregular no-enhancement ring may predict the risk of cervical LNM comparing with other three types of peripheral rings ( P = 0.04).…”
Section: Discussionmentioning
confidence: 99%
“…The staining for active MMP-9 in tumor tissue was graded as follows according to the staining intensity and distribution of immunoreactivity within a single tissue section 25 : (0) no reaction (−); (1) weak reaction (+); (2) moderate reaction (++); (3) intense reaction (+++). Immunohitochemical staining results was evaluated by two independent observers, with high concordance.…”
Section: Methodsmentioning
confidence: 99%
“…39 MMP9 is a cancer promoter in PTC, for example, MMP9 is up-regulated and correlates with tumour diameter, lymph node metastasis, degree of PTC infiltration and clinical stage. 40,41 We found that si-KDM1A reduced MMP9 expression and activation, suggesting that it may promote tumour progression by regulating MMP9.…”
Section: Discussionmentioning
confidence: 80%
“…2.475 mL (Merck KGaA, Darmstadt, Germany); 10 % (w/v) ammonium persulfate 0.1 mL (Sigma-Aldrich, St. Louis, USA); N , N , N’ , N’ tetramethylethylenediamine 0.01 mL (J.T.Baker Inc., Phillipsburg, NJ, USA); Sterile deionised water 4.625 mL)] with 0.1 % gelatin (Sigma-Aldrich, St. Louis, USA) as protease substrate [25]. After separation by electrophoresis, the gel was incubated in renaturation buffer (2.7 % Triton X-100 in distilled water) at room temperature with gentle shaking for 30 min.…”
Section: Methodsmentioning
confidence: 99%